The characterization of normal thyroid tissue by micro-FTIR spectroscopy - Pereira, Thiago M; Zezell, Denise M; Bird, Benjamin; Miljković, Milos; Diem, Max (Analyst (London), 2013)
In this paper, we report the spectral patterns of normal human thyroid tissue and methodology to interpret hyperspectral imaging data and protein conformational changes observed therein. Raw image datasets were imported into software written in-house in the MATLAB environment and processed to yield pseudo-color images of the tissue sections. All spectra were vector normalized, noise-filtered, and corrected for water-vapour contributions and scattering effects before being subjected to Hierarchical Cluster Analysis (HCA) and correlated with histological structures obtained from images of H&E-stained parallel tissue sections. We successfully identified a protein structural heterogeneity that can be correlated with the spatially resolved amount of iodine in the thyroglobulin structure of colloids and follicular cells.